Konsep dan Fenomena Konflik serta Cara Mengelola Konflik di SMK Ulumuddin - Titi, Dede; Tamsikudin, Tamsikudin (Jurnal Ilmiah Wahana Pendidikan, 2025)
The aim of this study is to understand the conflict management present in schools. The research employs a literature study approach, where all information is obtained from articles and books. The results and discussion indicate that the principal, as a school manager and educational leader, should consider various existing conflict management strategies. It is recommended to start with a passive attitude and gradually move towards an active orientation, depending on the maturity level of the parties involved in the conflict. Understanding how to change the attitudes and behaviors of those being led, as well as aspects related to power or authority, is crucial for better mastering conflict management. Another important aspect in using conflict management strategies is identifying the source of the conflict. Principally, the principal must possess power and authority as an educational leader. They must be able to utilize their inherent power and authority to guide the attitudes and behaviors of their subordinates. It cannot be implicitly generalized that conflict is either detrimental or beneficial. To ensure that conflict can enhance the performance and productivity of an organization, the organization's leader is required to have the ability to manage conflict. There are several conflict control techniques for various situations, each with its own advantages and disadvantages. Conflict needs to be addressed in a manner appropriate to its background. The causes of conflict stem not only from within the organization but also from external factors.